Drug-Induced Insomnia: Descriptive analysis of FDA Adverse Event Reporting System - Ahmed, Nehad J. (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: Insomnia is one the most common problems encountered by the family physician and can occur due to several causes such as using some drugs. The present study aimed to describe the reports that were submitted to FDA Adverse Event Reporting System (FAERS) about drug-induced insomnia. Materials and Methods: The FAERS was used to conduct this retrospective study that comprised a descriptive analysis of all reported adverse events of drug-induced insomnia in the past 5 years. Results: During the study period from the beginning of 2017 to the end of 2021, there were 86918 reports about drug-induced insomnia submitted to FAERS. The most frequently reported drugs were levothyroxine sodium (3.85%), duloxetine hydrochloride (3.24%), adalimumab (3.08%), pregabalin (2.71%), etanercept (2.17%), and niraparib (2.04%). Conclusion: It is important to increase the awareness of healthcare workers about the medications that could cause insomnia. Moreover, health-care providers should educate the patients about the drugs that could induce insomnia, how they can manage insomnia, and how they can report these adverse effects.